Construction of personal educational space of students in the field of physical culture based on the open education model - A. Shchekin; Yu. Zhuravleva; M. Katrenko; E. Yaroshenko (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the formation of an open educational space in the higher education system. Presented: the author’s vision of the studied phenomenon in the field of physical culture; a model of building students’ personal educational space in the field of physical culture, which makes it possible to activate their physical activity. The prospects and possibilities of implementing open information education in a modern university are shown, which contribute to the transition from teaching to self-learning, self-education in building an individual trajectory of students’ development in the field of physical culture.